ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN PLASTIK DAN KEMASAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ade Gunawan (Fakultas Ekonomi, Program Studi Akuntansi, Universitas Warmadewa, 2019)
This research was conducted to determine the cause of the decline and increase in the ratio of the company, and to find out and analyze the activity ratios and solvency ratios in measuring the financial performance of plastic and packaging companies listed on the Indonesia Stock Exchange for the 2012-2016 period. This type of research is descriptive, with 10 financial statements of tedftar plastic and packaging companies on the Indonesia Stock Exchange, with quantitative data and secondary data sources. In research and analyze financial performance by using activity ratios, namely inventory turnover and total assets turnover, solvency ratios, namely debt to asset ratio and debt to equity ratio. The results of the study show that the financial performance of plastic and packaging companies has decreased and increased not in accordance with standards effectiveness, this can be seen from the calculation of the activity and solvency ratios that have been carried out experiencing fluctuations and this results in some plastic and packaging companies not being good. Decreasing activity ratios occur due to the lack of the company's ability to manage inventory and the lack of companies utilizing their assets in producing efficient sales. As for the solvency ratio, it is still not optimal because there are still a number of plastic companies that have not been able to pay long-term obligations and too much debt that they have, so it is not comparable with the capital and assets owned by the company. Keywords: Activity; Financial Performance; Solvability